ANALISIS RASIO UNTUK MENGUKUR KINERJA PENGELOLAAN KEUANGAN DAERAH KOTA MALANG - Wahyuni, Nanik (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2010)
This research measures financial performance of local government (PAD) at Malang city using ratio analysis. Local government fund must be spent based on 3 E principles that is economic, efficient, and effective. Moreover, acountability is not simply showing the ability to expend public funds, but including on how to spend economically, efficient, and effective. The result indicates the average of PAD in Malang city is above 100%, although the regular expenses are still above PAD. Therefore, the dependence level to the central government is very high.Kata Kunci :Â  pengukuran kinerja, APBD, keuangan daerah, analisis ratio.